New and Accurate Online Self-Test Methods for Gain and Offset Errors of 10-Bit SAR-ADC - Mohammed Abdulmahdi Mohammedali; Qais Al-Gayem (Journal of Electrical and Computer Engineering)
The absolute quantization range of the successive approximation register (SAR) ADC is impacted by nonideality parameters like offset and gain error, which can make its performance at a lower level in high resolution applications. To decrease the conversion range error in ADC’s systems, this article proposes a static offset and an embedded gain error correction method. The proposed methods mainly include three stages: error modeling, error detection, and correction stages for both gain and offset. The main motivations for this method are simplicity, speed, and adaptability. To evaluate the accuracy, the technique of sinusoidal signals was used as the analog input signal. Gain error is reduced by 0.95% and the offsets are reduced by 98.7%.